Shoot him if he runs [large type] - Woods, Stuart (Woods, Stuart. Stone Barrington novel., 2007)
Stone Barrington and Holly Barker pursue a master spy and murderer in a tropical paradise where very little is as it seems. Teddy Fay, a rogue agent last seen escaping an imploding building in Iron Orchid, has been considered dead for some time now. But President Will Lee thinks Teddy may still be alive. In a top-secret Oval Office meeting, Stone learns that he and his cohorts, Holly Barker and Dino Baldachetti, are being sent to the beautiful Caribbean island of St. Marks, courtesy of the CIA, to track down Teddy once and for all. St. Marks is a vacationer's paradise, but its luxurious beach clubs and secluded mountain villas are home to corrupt local politicians and more than a few American ex-pats with murky personal histories. Stone and Holly soon discover that in St. Marks, everyone is hiding something, and Teddy Fay may just be hiding in plain sight.